Three decades of change in pancreatoduodenectomy and future prediction of pathological and operative complexity. Issue 3 (13th January 2022) - Halle-Smith, James M; Hodson, James; Coldham, Chris; Dasari, Bobby; Chatzizacharias, Nikolaos; Marudanayagam, Ravi; Sutcliffe, Robert; Isaac, John; Mirza, Darius F; Roberts, Keith J
Abstract : Despite increasing complexity of surgery and patient age, the duration of hospital stay and mortality rate after pancreatoduodenectomy are decreasing. Understanding changes over time permits an estimation of a future surgical cohort in which complexity will increase. It is important that surgeons continue to push boundaries.